Mutations and impaired function of LKB1 in familial and non-familial Peutz-Jeghers syndrome and a sporadic testicular cancer. - Ylikorkala, A; Avizienyte, E; Tomlinson, I; Tiainen, M; Roth, S; Loukola, A; Hemminki, A; Johansson, M; Sistonen, P; Markie, D; Neale, K; Phillips, R; et al. (1999)
Germline mutations in LKB1 have been reported to underlie familial Peutz-Jeghers syndrome (PJS) with intestinal hamartomatous polyps and an elevated risk of various neoplasms. To investigate the prevalence of LKB1 germline mutations in PJS more generally, we studied samples from 33 unrelated PJS patients including eight non-familial sporadic patients, 20 familial patients and five patients with unknown family history. Nineteen germline mutations were identified, 12 (60%) in familial and four (50%) in sporadic cases. LKB1 mutations were not detected in 14 (42%) patients, indicating that the existence of additional minor PJS loci cannot be excluded. LKB1 is predicted to encode a serine/threonine kinase. To demonstrate the putative Lkb1 kinase function and to study the consequences of LKB1 mutations in PJS and sporadic tumors, we have analyzed the kinase activity of wild-type and mutant Lkb1 proteins. Interestingly, while most of the small deletions or missense mutations resulted in loss-of-function alleles, one missense mutation (G163D) previously identified in a sporadic testicular tumor demonstrated severely impaired but detectable kinase activity.